Caracterización de las lesiones personales en el sistema estomatognático valoradas en el Instituto Nacional de Medina Legal y Ciencias Forenses, Regional Suroccidente, entre 2015 y 2020. - Castañeda, Lina-Alexandra; Quintero, María-Paula; Moreno-Correa, Sandra-Milena; Moreno-Gómez, Freddy; Vázquez-Escobar, Ruby-Amparo (Biomédica: Revista del Instituto Nacional de Salud, 2022)
Introduction: Personal injury forensic reports diagnose and define the damage to the body and health of a person including the stomatognathic system by injuries produced as the consequence of other people's actions. Objective: To characterize the personal injuries affecting the stomatognathic system as a result of violent actions in 266 cases evaluated at the Instituto Nacional de Medina legal y Ciencias Forenses-Regional Suroccidente (Cali, Colombia) between 2015 and 2020. Materials and methods: We conducted a descriptive cross-sectional study to characterize the personal injuries affecting the stomatognathic system. The information was taken from the personal injuries forensic reports registered on the Colombian forensic registration system (Sistema de Información Forense de Clínica de Colombia, SICLICO) platform and associated with the nature of the injury including its consequences and the medico-legal incapacity issued. Results: We observed a higher frequency of male aggressors (94.4%) and male victims (64.3%), especially in the age group between 21 and 30 years (32.6%). The most frequent contexts were interpersonal violence (76.3%) and intimate partner violence (19.9%). The main aggression mechanism was blunt trauma (88.0%). The lesions reported in soft tissues (83.5%) affected periodontal tissues (48.9%) and lips (28.6%) due to edema (32.7%) and wounds (22.9%) while in hard tissues (55.1%), they affected the teeth (41.4%) due to complicated fractures in the cervical third (19.2%) and avulsion (18%). Definitive disability predominated (64.7%) followed by 20-day disability (28.6%) and functional sequelae (24.1%). Conclusions: Periodontal tissues and teeth were the most affected structures causing considerable disabilities, as well as functional and aesthetic sequelae that mainly affected men in productive age.